(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The person who study the phenomena associated with the spread of technology cannot ignore a phenomenon that has spread remarkably and has become a title for the events that technology users face today. The most prominent of these phenomena is the phenomenon of selfie, which means that a person take a photo of himself somewhere, or in a certain situation, using a smart phone equipped with a digital device and then publishing it (for various reasons to be mentioned later) on social networks (Facebook, Twitter, And others .....). This phenomenon is not limited to a specific age group, but includes most age groups of different places and positions (simple people, celebrities of art literature and politics ....). Interestingly, it has become popular among teenagers, affecting them in general, and in their social relations in particular. It has spread like wildfire, to become a fashion among peoples, and addiction among other peoples. To the extent that it has been, since its emergence, a kind of mania and even a psychiatric illness to its users.